Using a route planner to optimize door-to-door visits for a pediatric home-hospitalization program: Feasibility study - Batlle, Astrid; Boada, Imma; Thió-Henestrosa, Santiago; Sevilla, Mariona Fernández de; García-García, Juan José (Frontiers in Pediatrics, 2022)
Background: Hospital Sant Joan de Déu (Barcelona) initiated a pediatric acute home-hospitalization program. Due to high patient turnover and the health staff’s lack of planning training, daily scheduling was a time-consuming task. Home-hospitalization planning is a vehicle routing problem that can be solved with a technological solution. It was therefore decided to evaluate the efficacy and necessity of the SmartMonkey.io planner. Objectives: To compare traditional manual route planning with a route optimizer, and to evaluate the technical feasibility of the implementation of a route planner into a homecare program. Methods: Eight participants (experienced homecare staff and inexperienced hospital staff) were included. Personal interviews were performed to assess their eagerness to try a technological solution to the planning problem. Objective benefits including reduced travel time (time planning, distance travelled and time travelled) were evaluated. Paired t-test, t-test, and Pearson’s correlation were used to compare manual and route planner scheduling. Participants then answered a questionnaire to assess planning difficulty and the acceptance of the route planner. Results: Homecare staff were initially reluctant to use the technology. Significant differences (P-value <.0001) in three variables were found between manual planning and the route planner. A moderate correlation between time planning and plan difficulty (r=0.59, P-value <.0001) was found with manual planning but not with the route planner. All route planner schedules saved time and distance. No significant differences were found between expertise and planning method. It was noted that it was easy to create plans with the route planner, while difficulty with manual planning grew as more locations were added. All participants evaluated the route planning tool favorably. Conclusions: Route-planning technology saved planning time and generated better plans than manual planning. The route planner’s learning curve was fast and results were obtained in the same amount of time regardless of difficulty and expertise. SmartMonkey.io also has the potential to reduce internal and environmental costs and increase staff productivity.